Approach Teacher Strategy for Digital Literacy in Pancasila Education Learning at Muhammadiyah 1 Vocational School, Sukoharjo - Garnis, Febrian Cantika; Patmisari, P (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study investigates the strategies teachers employ, the obstacles they face, and the solutions they devise when integrating Pancasila Education with digital‑literacy objectives at SMK Muhammadiyah 1 Sukoharjo. By examining how educators adapt civic and character education to leverage internet tools, the research aims to reveal effective practices and common challenges in fostering students’ digital competencies alongside their understanding of Pancasila values. Methodology: Adopting a descriptive qualitative approach, the study proceeded in three phases: problem identification, data collection, and analysis. Data were gathered at SMK Muhammadiyah 1 Sukoharjo through classroom observations of Pancasila lessons, semi‑structured interviews with school leaders, Pancasila Education teachers, and students, and document review of lesson plans and digital assignments. Thematic analysis was used to code and interpret patterns in teacher strategies, encountered barriers, and implemented remedies. Results: Findings show that teachers successfully integrate internet resources into Pancasila Education by assigning group projects that require students to research diverse online sources, encouraging collaborative inquiry and critical evaluation. Students generally respond positively to this digital approach. However, a major obstacle is students’ low reading motivation: many prefer instantaneous, entertaining online activities (such as gaming or social media) over more demanding research tasks. To address this, teachers have introduced gamified quizzes, multimedia presentations, and scaffolded reading guides to make digital research more engaging and manageable. Applications/Originality/Value: By documenting concrete strategies—such as collaborative web research and gamification of content— alongside practical solutions to boost reading engagement, this study offers a replicable framework for vocational schools aiming to strengthen both digital literacy and Pancasila values. Educational leaders and policymakers can leverage these insights to design teacher‑training programs and curriculum resources that balance immediate student interests with deeper, values‑based learning objectives in the digital age